Doped titanium magnesium phosphate solid electrolyte material and preparation method thereof

Through the design of doped titanium magnesium phosphate solid electrolyte material, the conductivity and stability problems of NASICON structural materials at room temperature are solved, the circulation and rate performance of lithium batteries are improved, and the commercial application potential of the materials is realized.

CN119240638APending Publication Date: 2025-01-03YIBIN NANMU NANO TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410836983.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-26
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The phosphate material with NASICON structure has low ionic conductivity, low grain boundary conductivity, poor stability and poor cycle life at room temperature, which limits its large-scale application in lithium batteries.

Method used

The chemical formula of the solid electrolyte material using doped titanium magnesium phosphate is Mg0.5Ti2-xMx(PO4)3, where the M elements are Zr and Mn. By introducing the doped metal M source, the Li+ transmission channel is adjusted and the lattice volume is increased. , reduce the diffusion activation energy of lithium ion and improve the conductivity of lithium ion.

Benefits of technology

The ionic conductivity of doped titanium magnesium phosphate solid electrolyte materials is significantly improved, the cycle performance, safety and rate performance of lithium batteries are improved, and the stability and life of NASICON structural materials are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240638A_ABST
    Figure CN119240638A_ABST
Patent Text Reader

Abstract

The invention provides a doped titanium magnesium phosphate solid electrolyte material and a preparation method thereof, the chemical general formula of the doped titanium magnesium phosphate solid electrolyte material is Mg0. 5Ti2-xMx (PO4) 3, the element M is at least one of Zr and Mn, and the value range of x is 0.1-0.6. The preparation method comprises the following steps: S1, adding a phosphorus source, a magnesium source, an M source, a titanium source and a sintering aid into a solvent, and sanding to obtain precursor slurry; s2, fully drying the precursor slurry to obtain a precursor; s3, performing high-temperature sintering on the precursor, performing heat preservation, and then performing cooling; and S4, crushing the cooled sintered product to obtain the doped titanium magnesium phosphate solid electrolyte material. The preparation method is simple, easy to operate and low in cost, the doped titanium magnesium phosphate solid electrolyte material with the NASICON structure is obtained by doping the metal M source, and the problems that in the prior art, a phosphate material is low in ionic conductivity, low in grain boundary conductivity, poor in stability and short in cycle life at normal temperature are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid electrolytes, and in particular relates to a doped magnesium titanium phosphate solid electrolyte material and a preparation method thereof. Background Art

[0002] In the rapid development of the battery industry in the past two decades, the electrolyte industry, as an important part of the upstream industrial chain, has developed rapidly. In particular, solid electrolyte materials have become a hot topic for scientific researchers due to their excellent conductivity and safety.

[0003] As lithium resources gradually decrease, finding new battery materials to replace lithium has become an urgent need of the industry. Among the many candidate elements, sodium, potassium, and magnesium have shown great potential due to their abundant reserves and similar chemical properties to lithium, especially magnesium. As a lightweight metal, magnesium is not only abundant on the earth, but also has similar chemical properties to lithium, similar ionic radius, and magnesium ions carry a double charge. These characteristics make magnesium an ideal battery material. In the process of exploring magnesium-based battery materials, NASICON structural materials have attracted attention due to their high safety and long life. This structural material has an open skeleton structure that can quickly diffuse ions. At the same time, during the embedding and migration of alkali metal ions or alkaline earth metal ions, the structure remains stable and is not prone to collapse, thereby ensuring the cycle life of the battery.

[0004] Titanium-based phosphate framework materials, as a type of NASICON structure, are favored for their high structural stability, easy production and rich structural diversity. Magnesium ions exhibit a stronger polarization effect than sodium ions due to their smaller atomic radius and higher specific surface charge density. Magnesium titanium phosphate (Mg 0.5 Ti2(PO4)3, referred to as MTP), also has a NASICON structure, and its application potential in lithium secondary batteries is comparable to that of lithium aluminum titanium phosphate.

[0005] However, although NASICON structural materials such as MTP have many advantages in theory, they still face some challenges in practical applications. For example, affected by the price of lithium minerals such as lithium carbonate, the cost of making lithium aluminum titanium phosphate is high, which limits the large-scale application of such materials. In addition, the ionic conductivity of MTP at room temperature is not high, the grain boundary conductivity is low, and the cycle life needs to be improved. The existence of these problems makes NASICON structured phosphate materials still a certain distance away from commercial application.

[0006] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention

[0007] In view of the shortcomings of the prior art described above, the object of the present invention is to provide a doped magnesium titanium phosphate solid electrolyte material and a preparation method thereof, which is used to solve the problems of low ionic conductivity, low grain boundary conductivity, poor stability and poor cycle life of NASICON structure phosphate materials in the prior art.

[0008] In order to achieve the above-mentioned object and other related objects, the present invention provides a doped magnesium titanium phosphate solid electrolyte material, wherein the chemical formula of the doped magnesium titanium phosphate solid electrolyte material is Mg 0.5 Ti 2-x M x (PO4)3, wherein the M element is at least one of Zr and Mn, and the value range of x is 0.1 to 0.6.

[0009] Preferably, the D50 particle size of the doped magnesium titanium phosphate solid electrolyte material is less than 1 μm.

[0010] The present invention also provides a method for preparing a doped magnesium titanium phosphate solid electrolyte material, characterized in that the preparation method comprises the following steps:

[0011] S1, adding a phosphorus source, a magnesium source, an M source, a titanium source and a sintering aid into a solvent and performing sand milling to obtain a precursor slurry;

[0012] S2, fully drying the precursor slurry to obtain a precursor;

[0013] S3, sintering the precursor in an oxygen-containing atmosphere at a high temperature and keeping the temperature for a period of time, and then cooling;

[0014] S4. The cooled sintered product is crushed to obtain a doped magnesium titanium phosphate solid electrolyte material.

[0015] Preferably, the phosphorus source in step S1 includes one or a combination of phosphorus pentoxide, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate.

[0016] Preferably, the magnesium source in step S1 includes one or a combination of magnesium carbonate, magnesium oxide and magnesium hydroxide.

[0017] Preferably, the M source in step S1 includes one or a combination of zirconium oxide, zirconium carbonate, zirconium hydroxide, zirconium n-propoxide, manganese dioxide, manganese carbonate, manganese tetraoxide, manganese oxide, and manganese trioxide.

[0018] Preferably, the titanium source in step S1 includes one or a combination of titanium dioxide and metatitanic acid.

[0019] Preferably, the molar ratio of the magnesium source, titanium source, M source and phosphorus source in step S1 is 0.5:(2-x):x:3, wherein 0.1≤x≤0.6, the magnesium source is calculated as Mg element, the titanium source is calculated as Ti element, the M source is calculated as M element, and the phosphorus source is calculated as P element.

[0020] Preferably, the sintering aid in step S1 is one or a combination of sucrose, glucose, oxalic acid, citric acid, and maltose, and the mass percentage of the sintering aid added in the precursor slurry is 0.01wt% to 1wt%.

[0021] Preferably, the solid content of the precursor slurry obtained in step S1 is 10 wt % to 40 wt %.

[0022] Preferably, the D50 particle size of the precursor slurry in step S1 is less than 1 μm.

[0023] Preferably, the drying method in step S2 includes one of air drying, vacuum drying and spray drying, and the drying temperature is 120°C to 180°C.

[0024] Preferably, the heating rate of the sintering in step S3 is 1-10° C. / min, the sintering temperature is 500° C.-1200° C., and the insulation time is 1 h-24 h.

[0025] As described above, the doped magnesium titanium phosphate solid electrolyte material and the preparation method thereof of the present invention have the following beneficial effects:

[0026] The preparation method provided by the present invention is simple in process, easy to operate and low in cost. The doping metal M source is introduced into the precursor slurry, and the Li + The transmission channel makes the ion conduction faster. After doping, the M atoms partially replace the titanium atoms, thereby increasing the volume of the lattice, increasing the size of the bottleneck path of lithium ion diffusion, reducing the activation energy of lithium ion diffusion, and providing sufficient exchange channels for lithium ions, thereby improving the lithium ion conductivity; and then through a sintering method, a NASICON structure doped magnesium titanium phosphate solid electrolyte material is obtained. The ion conductivity of the doped solid electrolyte material is greatly improved, which solves the problems of low ion conductivity, low grain boundary conductivity, poor stability and poor cycle life of the phosphate material of the NASICON structure at room temperature in the prior art. The cycle performance, safety and rate performance of the lithium battery prepared by adding it as a positive electrode material additive to the positive electrode slurry are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Shown is a SEM image of the solid electrolyte material in Example 1 of the present invention.

[0028] Figure 2 Shown is a SEM image of the solid electrolyte material in Comparative Example 1 of the present invention.

[0029] Figure 3 Shown is a SEM image of the solid electrolyte material in Comparative Example 2 of the present invention.

[0030] Figure 4 It shows a capacity comparison chart of the solid electrolyte materials in Example 1 of the present invention, Comparative Example 1 and Comparative Example 2 after being cycled for fifteen weeks at 1C / 1C and 5C / 1C respectively. DETAILED DESCRIPTION

[0031] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0032] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods in the following examples without specifying specific conditions are generally carried out under conventional conditions or under conditions recommended by the manufacturers.

[0033] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.

[0034] The present invention provides a doped magnesium titanium phosphate solid electrolyte material, the chemical formula of which is Mg 0.5 Ti 2-x M x (PO4)3, wherein the M element is at least one of Zr and Mn, and the value range of x is 0.1 to 0.6.

[0035] Specifically, the M element may be Zr or Mn alone, or a mixture of Zr and Mn, and the value of x may be within any range of 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, etc.

[0036] As an example, the D50 particle size of the doped magnesium titanium phosphate solid electrolyte material is less than 1 μm.

[0037] Specifically, the D50 particle size of the doped magnesium titanium phosphate solid electrolyte material may include values ​​within any range such as 100nm, 200nm, 400nm, 600nm, 800nm, 1μm, etc. The smaller the D50, the better, but it is not 0; D50 (volume median particle size) is an important parameter for characterizing the particle size distribution of the material. It is usually measured by a particle size analyzer and is used to describe the size and uniformity of the material particle size. D50 has an important influence on the electrochemical properties of the solid electrolyte material. A smaller particle size can provide a larger surface area, which helps to increase the contact area between the electrolyte material and the electrode material, thereby possibly improving the charge and discharge performance of the battery.

[0038] In addition, the present invention also provides a method for preparing a doped magnesium titanium phosphate solid electrolyte material, comprising the following steps:

[0039] S1, adding a phosphorus source, a magnesium source, an M source, a titanium source and a sintering aid into a solvent and performing sand milling to obtain a precursor slurry;

[0040] S2, fully drying the precursor slurry to obtain a precursor;

[0041] S3, sintering the precursor at high temperature in an oxygen-containing atmosphere and keeping the temperature for a period of time, and then cooling;

[0042] S4. The cooled sintered product is crushed to obtain a doped magnesium titanium phosphate solid electrolyte material.

[0043] Specifically, the preparation method provided by the present invention is simple in process, easy to operate, and low in cost. The doping metal M source is introduced into the precursor slurry, and the Li + The transmission channel makes the ion conduction faster. After doping, the M atoms partially replace the titanium atoms, thereby increasing the volume of the lattice, increasing the size of the lithium ion diffusion bottleneck path, reducing the activation energy of lithium ion diffusion, and providing sufficient exchange channels for lithium ions, thereby improving the lithium ion conductivity; the ionic conductivity of the solid electrolyte material after doping is greatly improved, which solves the problems of low ionic conductivity, low grain boundary conductivity, poor stability and poor cycle life of the phosphate material with NASICON structure in the prior art at room temperature.

[0044] Specifically, in step S1, the sand grinding media are zirconium beads and alumina beads, and the particle size is less than 10 mm, and no excessive restriction is made here; a sintering aid is also added in this step, and the addition of the sintering aid inhibits adhesion during crystal growth.

[0045] As an example, the phosphorus source includes one or a combination of phosphorus pentoxide, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate.

[0046] As an example, the magnesium source includes one or a combination of magnesium carbonate, magnesium oxide, and magnesium hydroxide.

[0047] As an example, the M source includes one or a combination of zirconium oxide, zirconium carbonate, zirconium hydroxide, zirconium n-propoxide, manganese dioxide, manganese carbonate, trimanganese tetraoxide, manganese oxide, and dimanganese trioxide.

[0048] As an example, the titanium source includes titanium dioxide, metatitanic acid, or a combination thereof.

[0049] As an example, in step S1, the molar ratio between the magnesium source, titanium source, M source, and phosphorus source is 0.5:(2-x):x:3, where 0.1≤x≤0.6, the magnesium source is calculated as Mg element, the titanium source is calculated as Ti element, the M source is calculated as M element, and the phosphorus source is calculated as P element.

[0050] Specifically, the value of x may include values ​​within any range such as 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, etc.

[0051] Specifically, the ion occupancy rate of lithium ions is adjusted by different doping elements M and doping contents, making ion conduction faster. The partial substitution of Mn and Zr atoms for titanium atoms increases its lattice volume, increases the diffusion channels of lithium ions, reduces the activation energy of lithium ion diffusion, and thus improves ionic conductivity.

[0052] As an example, the sintering aid in step S1 is one or a combination of sucrose, glucose, oxalic acid, citric acid, and maltose, and the mass percentage of the sintering aid added in the precursor slurry is 0.01 wt % to 1 wt %.

[0053] Specifically, the mass percentage of the sintering aid added in the precursor slurry in step S1 may include values ​​within any range such as 0.01wt%, 0.05wt%, 0.1wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1wt%, etc.

[0054] As an example, the solid content of the precursor slurry obtained in step S1 is 10 wt % to 40 wt %.

[0055] Specifically, the solid content of the precursor slurry obtained in step S1 may include values ​​within any range such as 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, etc.

[0056] As an example, the D50 particle size of the precursor slurry in step S1 is less than 1 μm.

[0057] Specifically, the D50 particle size of the precursor slurry may include values ​​within any range such as 100nm, 200nm, 400nm, 600nm, 800nm, 1μm, etc.; the D50 particle size of the precursor slurry can ensure the quality of the electrode and the performance of the battery. A larger D50 value means that the slurry contains more large particles, which may lead to a lower viscosity of the slurry, which is conducive to increasing the solid content and reducing the difficulty of coating. However, if the particles are too large, it may affect the charge and discharge performance and cycle stability of the electrode; a smaller D50 value indicates that the slurry contains more small particles, which may increase the utilization rate and specific surface area of ​​the active material of the electrode, thereby facilitating the charge transfer at the electrode / electrolyte interface and increasing the specific capacity. As an example, the drying method in step S2 includes one of blast drying, vacuum drying, and spray drying, and the drying temperature is 120°C to 180°C.

[0058] Specifically, the drying temperature in step S2 may include values ​​within any range such as 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, etc.

[0059] As an example, the heating rate of sintering in step S3 is 1-10° C. / min, the sintering temperature is 500° C.-1200° C., and the holding time is 1 h-24 h.

[0060] Specifically, the heating rate of sintering in step S3 may include a value within any range such as 1°C / min, 2°C / min, 4°C / min, 6°C / min, 8°C / min, 10°C / min, etc., the sintering temperature may include a value within any range such as 500°C, 600°C, 800°C, 1000°C, 1100°C, 1200°C, etc., and the insulation time may include a value within any range such as 1h, 4h, 8h, 12h, 16h, 20h, 24h, etc.

[0061] In order to better understand the doped magnesium titanium phosphate solid electrolyte material and the preparation method thereof in the present invention, the doped magnesium titanium phosphate solid electrolyte material and the preparation method thereof in the present invention are described below with reference to specific embodiments. It should be noted that these embodiments are merely descriptive and do not limit the present invention in any way.

[0062] Example 1

[0063] This embodiment provides a method for preparing a doped magnesium titanium phosphate solid electrolyte material, comprising the following steps:

[0064] S1. Add 3450.78 g of phosphorus source (monoammonium phosphate), 421.6 g of magnesium source (magnesium carbonate), 1517.53 g of titanium source (titanium dioxide), 123.22 g of M source (zirconium oxide) and 36.4 g of sintering aid (sucrose) into water for sand grinding to obtain 36341 g of precursor slurry with a D50 particle size of 0.741 μm; wherein the solid content of the precursor slurry is 10%, and the amount of the sintering aid added is 0.1 wt% of the mass of the precursor slurry;

[0065] S2, vacuum drying the precursor slurry at 120° C. to obtain a precursor;

[0066] S3, placing the precursor in a ceramic sagger, heating it to 1000°C at a heating rate of 5°C / min in an atmosphere of air, sintering it for 10 hours, and then cooling it;

[0067] S4. The cooled sintered product is crushed to obtain a doped magnesium titanium phosphate solid electrolyte material.

[0068] This embodiment also provides a doped magnesium titanium phosphate solid electrolyte material, whose chemical formula is Mg 0.5 Ti 1.9 M 0.1 (PO4)3, wherein the M element is Zr and x is 0.1.

[0069] See also Figure 1 This is a SEM image of the doped magnesium titanium phosphate solid electrolyte material in this embodiment. It can be seen from the figure that the doped magnesium titanium phosphate solid electrolyte material prepared in this embodiment has mesoporous pores with fine particles attached to the surface, which can improve the interface contact of the material and reduce the interface impedance.

[0070] Example 2

[0071] This embodiment provides a method for preparing a doped magnesium titanium phosphate solid electrolyte material, comprising the following steps:

[0072] S1. Add 4473.6 g of phosphorus source (ammonium phosphate), 201.5 g of magnesium source (magnesium oxide), 1357.79 g of titanium source 17 mol (titanium dioxide), 369.7 g of M source 3 mol (zirconium oxide) and 170.4 g of sintering aid (glucose) into water for sand grinding to obtain 85195.8 g of precursor slurry with a D50 particle size of 0.341 μm; wherein the solid content of the precursor slurry is 20 wt%, and the amount of the sintering aid added is 0.2 wt% of the mass of the precursor slurry;

[0073] S2, vacuum drying the precursor slurry at 140° C. to obtain a precursor;

[0074] S3, placing the precursor in a ceramic sagger, heating it to 1100°C at a heating rate of 5°C / min in an atmosphere of air, sintering it for 10 hours, and then cooling it;

[0075] S4. The cooled sintered product is crushed to obtain a doped magnesium titanium phosphate solid electrolyte material.

[0076] This embodiment also provides a doped magnesium titanium phosphate solid electrolyte material, whose chemical formula is Mg 0.5 Ti 1.7 M 0.3 (PO4)3, wherein the M element is Zr and x is 0.3.

[0077] Example 3

[0078] This embodiment provides a method for preparing a doped magnesium titanium phosphate solid electrolyte material, comprising the following steps:

[0079] S1. Add 3961.68 g of phosphorus source (diammonium hydrogen phosphate), 421.55 g of magnesium source (magnesium oxide), 1622.18 g of titanium source (metatitanic acid), 1267.44 g of M source (zirconium carbonate) and 126.3 g of sintering aid (glucose) into water for sand milling to obtain 12633 g of precursor slurry with a D50 particle size of 0.341 μm; wherein the solid content of the precursor slurry is 40 wt %, and the amount of the sintering aid added is 1 wt % of the mass of the precursor slurry;

[0080] S2, vacuum drying the precursor slurry at 120° C. to obtain a precursor;

[0081] S3, placing the precursor in a ceramic sagger, heating it to 1100°C at a heating rate of 3°C / min in an atmosphere of air, sintering it for 10 hours, and then cooling it;

[0082] S4. The cooled sintered product is crushed to obtain a doped magnesium titanium phosphate solid electrolyte material.

[0083] This embodiment also provides a doped magnesium titanium phosphate solid electrolyte material, whose chemical formula is Mg 0.5 Ti 1.4 M 0.6 (PO4)3, wherein the M element is Zr and x is 0.6.

[0084] Example 4

[0085] This embodiment provides a method for preparing a doped magnesium titanium phosphate solid electrolyte material, comprising the following steps:

[0086] S1. Add 2129.18 g of phosphorus source (phosphorus pentoxide), 291.6 g of magnesium source (magnesium hydroxide), 1325.8 g of titanium source (titanium dioxide), 295.6 g of M source (manganese dioxide) and 43 g of sintering aid (oxalic acid) into water for sand grinding to obtain 14446 g of precursor slurry with a D50 particle size of 0.474 μm; wherein the solid content of the precursor slurry is 30 wt%, and the amount of the sintering aid added is 0.3 wt% of the mass of the precursor slurry;

[0087] S2, vacuum drying the precursor slurry at 135° C. to obtain a precursor;

[0088] S3, placing the precursor in a ceramic sagger and heating it to 1100°C at a heating rate of 4°C / min in an atmosphere of air and sintering for 8 hours, and then cooling;

[0089] S4. The cooled sintered product is crushed to obtain a doped magnesium titanium phosphate solid electrolyte material.

[0090] This embodiment also provides a doped magnesium titanium phosphate solid electrolyte material, whose chemical formula is Mg 0.5 Ti 1.66 M 0.34 (PO4)3, wherein the M element is Mn and x is 0.34.

[0091] Example 5

[0092] This embodiment provides a method for preparing a doped magnesium titanium phosphate solid electrolyte material, comprising the following steps:

[0093] S1. Add 1320.56 g of phosphorus source (phosphorus pentoxide), 421.55 g of magnesium source (magnesium carbonate), 1738 g of titanium source (metatitanic acid), 394.7 g of M source (manganese trioxide) and 50.2 g of sintering aid (oxalic acid) into water for sand grinding to obtain 21482 g of precursor slurry with a D50 particle size of 0.274 μm; wherein the solid content of the precursor slurry is 20 wt%, and the amount of the sintering aid added is 0.23 wt% of the mass of the precursor slurry;

[0094] S2, vacuum drying the precursor slurry at 130° C. to obtain a precursor;

[0095] S3, placing the precursor in a ceramic sagger, heating it to 1100°C at a heating rate of 3°C / min in an atmosphere of air, sintering it for 8 hours, and then cooling it;

[0096] S4. The cooled sintered product is crushed to obtain a doped magnesium titanium phosphate solid electrolyte material.

[0097] This embodiment also provides a doped magnesium titanium phosphate solid electrolyte material, whose chemical formula is Mg 0.5 Ti 1.5 M 0.5 (PO4)3, where the M element is Mn and x is 0.5.

[0098] Comparative Example 1

[0099] This comparative example provides a method for preparing a magnesium titanium phosphate solid electrolyte material, comprising the following steps:

[0100] S1. Mix 3450.78 g of a phosphorus source (ammonium dihydrogen phosphate), 421.55 g of a magnesium source (magnesium carbonate), and 1597.4 g of a titanium source (titanium dioxide) to obtain a mixed powder;

[0101] S2, placing the mixed powder in a ceramic sagger, heating it to 1000°C at a heating rate of 5°C / min in an atmosphere of air, sintering it for 12 hours, and then cooling it;

[0102] S4. The cooled sintered product is crushed to obtain a magnesium titanium phosphate solid electrolyte material.

[0103] This comparative example also provides a magnesium titanium phosphate solid electrolyte material, whose chemical formula is Mg 0.5 Ti2(PO4)3, where x is 0.

[0104] See also Figure 2 : is a SEM picture of the magnesium titanium phosphate solid electrolyte material in this comparative example. It can be seen from the picture that the single crystal volume of the magnesium titanium phosphate solid electrolyte material prepared in this comparative example is relatively large, which increases the subsequent processing cost.

[0105] Comparative Example 2

[0106] This comparative example provides a method for preparing a magnesium titanium phosphate solid electrolyte material, comprising the following steps:

[0107] S1. Add 1150.26 g of phosphorus source (ammonium dihydrogen phosphate), 843.1 g of magnesium source (magnesium carbonate), and 1597.4 g of titanium source (titanium dioxide) into water for sand grinding to obtain 36341 g of precursor slurry with a D50 particle size of 0.741 μm;

[0108] S2, vacuum drying the precursor slurry at 120° C. to obtain a precursor;

[0109] S3, placing the precursor in a ceramic sagger, heating it to 1000°C at a heating rate of 5°C / min in an atmosphere of air, sintering it for 12 hours, and then cooling it;

[0110] S4. The cooled sintered product is crushed to obtain a magnesium titanium phosphate solid electrolyte material.

[0111] This comparative example also provides a magnesium titanium phosphate solid electrolyte material, whose chemical formula is Mg 0.5 Ti2(PO4)3, where x is 0.

[0112] Performance Testing:

[0113] The conductivity test was performed on the doped magnesium titanium phosphate solid electrolyte material provided in Examples 1 to 5 and the magnesium titanium phosphate solid electrolyte material in Comparative Examples 1 to 2. The specific test method is: the doped magnesium titanium phosphate solid electrolyte material or the magnesium titanium phosphate solid electrolyte material is pressed into a sheet at a pressure of 200 MPa using a powder tablet press, and then both sides of the sheet are polished with sandpaper and coated with conductive silver paste respectively. After drying, an electrochemical impedance spectroscopy (EIS) test is performed on it using an electrochemical tester. The measured ionic conductivity results are shown in Table 1.

[0114] Table 1. Ionic conductivity of the doped magnesium titanium phosphate solid electrolyte materials in Examples 1 to 5 and the magnesium titanium phosphate solid electrolyte materials in Comparative Examples 1 to 2

[0115]

[0116]

[0117] The solid electrolyte prepared in Example 1, Comparative Example 1 and Comparative Example 2 was respectively mixed with NCM523, SP (carbon black, used as a conductive agent), CNT (carbon nanotube), and PVDF (polyvinylidene fluoride) in a mass ratio of 1:96:1:1:1 to prepare a positive electrode slurry coated with aluminum foil, and graphite was coated on a copper foil as the negative electrode side. The N / P ratio (molar ratio of the positive electrode material to the negative electrode material) was designed to be 1.2 to prepare a ternary full battery. The battery was charged and discharged at a current rate of 1C for 15 weeks on a test cabinet, and then charged and discharged at a current rate of 5C for 15 weeks. See FIG. Figure 4 The lithium battery made by adding the doped magnesium titanium phosphate solid electrolyte material as a positive electrode material additive to the positive electrode slurry has good cycle performance.

[0118] In summary, the preparation method provided by the present invention is simple in process, easy to operate, and low in cost. The doping metal M source is introduced into the precursor slurry, and the Li +The transmission channel makes the ion conduction faster. After doping, the M atoms partially replace the titanium atoms, thereby increasing the volume of the lattice, increasing the size of the bottleneck path of lithium ion diffusion, reducing the activation energy of lithium ion diffusion, and providing sufficient exchange channels for lithium ions, thereby improving the lithium ion conductivity; and then through a sintering method, the doped magnesium titanium phosphate solid electrolyte material with NASICON structure is obtained. The ionic conductivity of the electrolyte material after doping is greatly improved, which solves the problem that the phosphate material with NASICON structure at room temperature has low ionic conductivity, low grain boundary conductivity, poor stability, and poor cycle life in the prior art. The cycle performance, safety, and rate performance of the lithium battery prepared by adding it as a positive electrode material additive to the positive electrode slurry are all improved. Therefore, the present invention effectively overcomes the various shortcomings in the prior art and has a high industrial utilization value.

[0119] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A doped magnesium titanium phosphate solid electrolyte material, characterized in that: The chemical formula of the doped magnesium titanium phosphate solid electrolyte material is Mg 0.5 Ti 2-x M x (PO4)3, wherein the M element is at least one of Zr and Mn, and the value range of x is 0.1 to 0.

6.

2. The doped magnesium titanium phosphate solid electrolyte material according to claim 1, characterized in that: The D50 particle size of the doped magnesium titanium phosphate solid electrolyte material is less than 1 μm.

3. A method for preparing a doped magnesium titanium phosphate solid electrolyte material, characterized in that: The preparation method comprises the following steps: S1, adding a phosphorus source, a magnesium source, an M source, a titanium source and a sintering aid into a solvent and performing sand milling to obtain a precursor slurry; S2, fully drying the precursor slurry to obtain a precursor; S3, sintering the precursor in an oxygen-containing atmosphere at a high temperature and keeping the temperature for a period of time, and then cooling; S4. The cooled sintered product is crushed to obtain a doped magnesium titanium phosphate solid electrolyte material.

4. The method for preparing the doped magnesium titanium phosphate solid electrolyte material according to claim 1, characterized in that: Step S1 includes one or a combination of the following conditions: The phosphorus source includes one or a combination of phosphorus pentoxide, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium phosphate; The magnesium source includes one or a combination of magnesium carbonate, magnesium oxide, and magnesium hydroxide; The M source includes one or a combination of zirconium oxide, zirconium carbonate, zirconium hydroxide, zirconium n-propoxide, manganese dioxide, manganese carbonate, manganese tetraoxide, manganese oxide, and manganese trioxide; The titanium source includes one or a combination of titanium dioxide and metatitanic acid.

5. The method for preparing the doped magnesium titanium phosphate solid electrolyte material according to claim 1, characterized in that: The molar ratio of the magnesium source, titanium source, M source and phosphorus source in step S1 is 0.5:(2-x):x:3, wherein 0.1≤x≤0.6, the magnesium source is calculated as Mg element, the titanium source is calculated as Ti element, the M source is calculated as M element, and the phosphorus source is calculated as P element.

6. The method for preparing the doped magnesium titanium phosphate solid electrolyte material according to claim 1, characterized in that: The sintering aid in step S1 is one or a combination of sucrose, glucose, oxalic acid, citric acid, and maltose, and the mass percentage of the sintering aid added in the precursor slurry is 0.01wt% to 1wt%.

7. The method for preparing the doped magnesium titanium phosphate solid electrolyte material according to claim 1, characterized in that: The solid content of the precursor slurry obtained in step S1 is 10 wt % to 40 wt %.

8. The method for preparing the doped magnesium titanium phosphate solid electrolyte material according to claim 1, characterized in that: The D50 particle size of the precursor slurry in step S1 is less than 1 μm.

9. The method for preparing the doped magnesium titanium phosphate solid electrolyte material according to claim 1, characterized in that: The drying method in step S2 includes one of air drying, vacuum drying and spray drying, and the drying temperature is 120°C to 180°C.

10. The method for preparing the doped magnesium titanium phosphate solid electrolyte material according to claim 1, characterized in that: The heating rate of the sintering in step S3 is 1-10°C / min, the sintering temperature is 500°C-1200°C, and the insulation time is 1h-24h.